Long-term outcome of paediatric patients with hereditary tubular disorders - Haffner, Dieter; Weinfurth, Achim Michael; Manz, Friedrich; Schmidt, Hildgund; Bremer, Hans J.; Mehls, Otto; Schärer, Karl (Nephron, 1999)
Background: An increasing number of children with hereditary tubular disorders (HTD) reach adult life due to diagnostic and therapeutic advances which results in growing need to manage these patients by adult centres. Data on the prevalence and the late clinical problems of these patients are limited. Methods: We observed 177 paediatric patients with isolated or complex HTD between 1969 and 1994. The median age at the time of diagnosis was 3 (range 0-18) years and the median observation period 10 (range 1-43) years. The long-term outcomes with respect to renal function, bone disease, and body growth were analyzed. Results: The prevalence of HTD was 3.2% of all patients observed in our renal unit and 14% of those patients with chronic renal failure and/ or end-stage renal disease. The three most frequent disorders observed were nephropathic cystinosis (n = 34), X-linked hypophosphataemic rickets (n = 26), and idiopathic hypercalciuria (n = 17). At the last observation, 12% of the patients with isolated HTD and 30% of those with complex HTD had developed preterminal chronic renal failure; end-stage renal disease was observed in 5 and 25%, respectively (p < 0.001). Progressive disease occurred mainly in patients having cystinosis, primary hyperoxaluria, the syndrome of hypomagnesaemia/hypercalciuria, primary Fanconi syndrome, Fanconi-Bickel syndrome, and methylmalonic aciduria. Nephrocalcinosis was found in 42%, urolithiasis in 14%, bone deformities and/or fractures in 28%, and other extrarenal alterations in 29% of all patients. The median body height at last observation was 2.0 SD below the normal mean (range from -10.4 to +2.6), and the adult height was subnormal in 48% of 67 grown-up patients. Growth retardation was more severe in complex than in isolated HTD. The mortality decreased from 17% in 1969-1981 to 12% in 1982-1994. Conclusion: Although HTD are rare nephropathies, their frequently progressive course associated with extrarenal complications requires the attention of nephrologists beyond the paediatric age.